Fuel for inequality: Distributional effects of environmental reforms on private transport - Miguel Angel Tovar Rea\~nos; Katrin Sommerfeld (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2016)
This paper provides the first empirical evidence of the distributional effects of subsidies for the purchase of alternative vehicles based on an extended version of Hausman's exact consumer surplus. Consistently with economic theory, we estimate changes in household welfare, inequality and social welfare corresponding to different reforms. First, we find that an additional tax on conventional fuel is regressive. However, returning the additional tax revenue via lump-sum transfers can alleviate this effect. Second, when the additional revenue is also used to finance subsidies for electrical and compressed natural gas (CNG) vehicles, households that own such vehicles experience welfare gains. However, this policy also increases income inequality and decreases social welfare.
urn:nbn:de:bsz:180-madoc-418208
Keywords: Q41; R48; C33; 330; Transport policies; Distributional effects; Electrical vehicles; Passenger cars